A Study of Climate-Smart Farming Practices and Climate-resiliency Field Schools in Mindanao, the Philippines. (October 2017) - Chandra, Alvin; Dargusch, Paul; McNamara, Karen E.; Caspe, Ana Maria; Dalabajan, Dante
Highlights: We examine Climate-Smart Agriculture practices implemented by Climate-resiliency Field Schools in Mindanao, the Philippines. We demonstrate that climate-smart interventions are location-specific, technically rigorous and knowledge-intensive. The addition of adaptation and food production outcomes strengthened mitigation to climate change outcomes (and vice versa). Climate-Smart Agriculture practices with a strong livelihood component are generally favored by smallholder farmers. Climate-resiliency Field Schools is effective in advancing local-level trilateral climate-smart interventions. Summary: This paper explores how Climate-resiliency Field Schools involving smallholder farmers in the Mindanao region of the Philippines advance climate-smart farming practices. Using data from field observations, 86 interviews, and 13 focus group discussions from five municipalities, the research finds that cross-scale activities, including local plans and multi-stakeholder forums, and municipal budgeting processes, influence adaptation and mitigation to climate change in smallholder farming systems. Furthermore, using matrix analysis and stakeholder responses, we identify interactions, synergies, conflicts, and potential co-benefits between mitigation and adaptation, and food production practices. The analysis of climate-resiliency field school practices shows that the addition of livelihood outcomes to smallholder farming landscapes strengthen adaptation, mitigation, and food production outcomes (and vice versa). Climate-resiliency Field Schools have promoted the practice of organic farming, various systems for rice intensification, and the establishment of community seed banks. Other practices, such as soil conservation, reforestation, and agroforestry, have been used in Mindanao to maintain carbon stocks while increasing crop production. Climate-resiliency Field Schools serve as a multilevel institutional platform where farmers can access climate information, which they can use to improve farm planning (i.e., choices of crops, timing of farm preparation, and harvest). The research findings suggest that climate-smart interventions are highly location-specific, technically rigorous, involve knowledge-intensive processes, and are influenced by the knowledge and capacities of local farming communities and implementing partners. We conclude with some suggestions for the design of programs, and the types of interventions that are required to sustain and ultimately scale up efforts to enhance climate-smart agriculture.